The Valuation of Forest characteristics - Nick Hanley; Robin Ruffell (Queen's University, Department of Economics, 1992)
Most work on valuing the recreational benefits of public forests has concentrated on arriving at consumers surplus per visit figures, using either the travel cost method, or contingent valuation. We use both methods to try and explain the variation in consumers surplus across different forest types, by placing values on the physical characteristics of individual forests. These characteristics are also used to explain total visits to a given forest. Both maximum likelihood and ordinary least squares estimates are presented.
Keywords: 330; non-market good valuation; consumers surplus; forestry economics